Implementation of Sociometry in Guidance and Counseling: A Systematic Thematic Review (2000–2023) - Susanto, Eko; Novitasari, Yuni (Universitas Muhammadiyah Metro, 2024)
Sociometry is a method for assessing social relationships within groups developed by Jacob L. Moreno and has long been applied in guidance and counseling. This study aims to analyze the implementation of sociometry in guidance and counseling during the period 2000–2023 through a systematic thematic review approach. Data sources came from 42 open-access primary references cited in a recent systematic literature review. The thematic analysis identified five main themes: (1) theoretical foundations and validity of sociometry; (2) the evolution of applications from individual diagnostics to systemic analysis; (3) intervention effectiveness and stability of social status; (4) practical and ethical challenges in the school context; and (5) the paradox between scientific validity and practicality of implementation. The results indicate that sociometry remains recognized as the gold standard for measuring social status, peer relationships, and classroom climate, with convergent validity confirmed through significant correlations with standard instruments such as the SSRS and CBCL (r = −.20 to .24, p < .01). However, its implementation faces serious obstacles: high stability of rejected status (e.g., children with ADHD are more likely to be rejected even after intensive intervention), the risk of stigmatization, time and training constraints, and a gap between theoretical validity and practical adoption (only 3.64% of US schools use it for universal screening). Key gaps include the paucity of research on the fidelity-effectiveness relationship, the lack of modern psychometric validation, and the dominance of Western contexts. Recommendations include the adoption of the more accurate García Bacete (GB) classification model (92.3% behavioral validity for neglected status), the use of sociometry as a triangulation tool, the development of web-based digital tools, and ethical training for counselors and teachers. This study provides conceptual and practical contributions to strengthening evidence-based counseling in Indonesia and globally.